A fluorescence-LC method with NDA pre-column derivatization for fumonisin B2 determination in black aspergilli cultures - Abrunhosa, Luís (2011)
The recent discovery that Aspergillus niger can produce fumonisins raises a new mycotoxigenic risk that requires additional studies to assess the impact on agricultural commodities. Here, we report the development and validation of a sensitive LC-fluorescence method for the identification of fumonisin B2 in black aspergilli cultures. The performances of naphthalene-2,3-- dicarboxaldehyde (NDA), o-phthaldialdehyde (OPA), and 9-fluorenylmethyl chloroformate (FMOC) for the precolumn derivatization of samples were evaluated and compared. The best methodology included the following elements: NDA was used during pre-column derivatization; the derivatives were separated by a 30min isocratic elution with acetonitrile=H2O=acetic acid (60:40:1, v=v=v), pumped at a flow rate of 1mL min 1 on a polar C18 reversed-phase YMC-Pack ODS-AQ column (250 4.6mm, 5 lm); and fluorescence detection using excitation and emission wavelengths of 420 and 500 nm, respectively. The calibration curve was found to give a good linear response (r2>0.9999) from 1 to 200 lg L 1. For FB2, which is the main fumonisin detected in black aspergilli thus far, this method measured an LOD and an LOQ of 2 and 6 lg kg 1, respectively. Using this method, the amount of FB2 in black aspergilli cultures can be simply and rapidly determined.